Challenges in Accessing Health Care Management for People with Disability in Pakistan - Kiran Siddiquie, Muhammad Asif Chuadhry, Asim Ahmed (JIE, 2023)
This study examines how the lives of disabled people are challenged physically, financially and due to specialists’ attitudes towards them while accessing health care management in disability centers of Rawalpindi and Islamabad. These challenges must be accommodated them in society and uphold their rights by enabling the disabled with a peaceful and productive life. Moreover, for develop firm recommendations for future policy implications and provide the researchers with a better understanding of the demographic characteristics of disabled persons in Pakistan.